The TARGET_TIA: A complete, flexible and sound territorial impact assessment tool - Medeiros, E. (2022)
This chapter presents TARGET_TIA as a relevant and flexible Territorial Impact Assessment (TIA) methodology. TARGET_TIA was created in a context where existing ESPON TIA tools were mainly designed for assessing ex ante territorial impacts of EU directives. Hence, in view of the need to properly assess the main ex post territorial impacts of EU Cohesion Policy in several countries in a relevant and sound way, the author decided to design, test and apply his own TIA methodology, named TARGET_TIA. When compared with other existing TIA methodologies, TARGET_TIA can be used both at ex ante and ex post policy evaluation phases. In addition, it brings to the table the possibility to use counterfactual evaluation elements to allow the production of credible and sound TIA evaluation scores. Following on from its implementation in assessing the main territorial impacts of EU policies and programmes, mostly at the ex post evaluation phase, it is possible to conclude that it is a credible, flexible, easy-to-operate, cost-effective and robust TIA methodology, which can be applied to projects, programmes and policies, at all territorial levels.